The Destructive Power of False Ideals: A Reassessment of Arthur Miller’s Death of a Salesman - Ahmed Saeed Ahmed Mocbil (Journal of Philology and Educational Sciences)
This research critically examines the impact of false ideals on the central characters in Arthur Miller’s Death of a Salesman. The paper employs a qualitative method that includes close reading and thematic analysis. The study reassesses themes of disillusionment, the American Dream, and the consequences of pursuing unattainable aspirations. The findings reveal that the characters’ adherence to these false ideals leads to significant emotional distress and fractured familial relationships. The analysis highlights how societal pressures shape individual identities and contribute to the characters’ tragic downfalls, particularly through Willy Loman's misguided beliefs in popularity and material success. This research offers new ideas about why the play still matters today. It shows that Miller’s work warns us about focusing too much on looks instead of real happiness. The findings suggest we should rethink our current values and how they affect our mental health and family life.